In situ FTIR analysis for the determination of imidization degree of polyimide precursors. (3rd January 2022) - Zhang, Yuanming; Mushtaq, Nafeesa; Fang, Xingzhong; Chen, Guofei
Abstract: Two series of polyimide (PI) precursors, poly(amic acid) (PAA) and poly(amic acid) salt (PAAS) were prepared from biphenyltetracarboxylic dianhydride (BPDA) and 2, 2′-bis(trifluoromethyl)-[1, 1′-biphenyl]-4, 4′-diamine (TFDB) monomers, and systematically studied for thermal imidization. Firstly, the temperature for the complete thermal imidization of two precursors was determined by the thermogravimetric analysis (TGA). Later, a new method for the determination of the imidization degree (ID) was proposed by in situ infrared spectroscopy, and it was inferred that the traditional method for ID calculation is no longer applicable to PI precursors with aromatic base. The ID and the kinetics of thermal imidization of the aforementioned two precursors were also investigated by the new method. In comparison to PAA, PAAS exhibited higher imidization rate and lower temperature for thermal imidization. Graphical abstract: Image 1 Highlights: Two polyimide precursors-PAA and PAAS were synthesized. For the precursors containing aromatic base, the in situ infrared method to calculate the ID was proposed. The imidization progress of PAAS precursors occurs mainly at low temperature and at a high rate.